Estimation of the morphology development of immiscible liquid-liquid systems during single screw extrusion - Gaspar-Cunha, A. (2010)
A mathematical model to predict the evolution of the morphology of immiscible liquid-liquid systems in single screw extruders has been developed. The model computes the dimensions of the dispersed phase in the polymeric matrix, taking into account the stretching, break-up, and coalescence phenomena. The corresponding routine was inserted in a process modeling software, describing the flow in a single screw extruder from hopper do die. The drop dimensions were computed along the melting and melt conveying zones. This enabled the study of the morphological evolution of a two-phase liquid system in a single screw extruder, taking into consideration the effects of the material properties, operating conditions, and screw geometry. The limited experimental data obtained was generally in line with the theoretical predictions. POLYM. ENG. SCI., 50:2194-2204, 2010. (C) 2010 Society of Plastics Engineers